2012
DOI: 10.2485/jhtb.21.25
|View full text |Cite
|
Sign up to set email alerts
|

Bone Regeneration by Demineralized Dentin Matrix in Skull Defects of Rats

Abstract: Alveolar bone defects may result in functional and morphological abnormalities. In such cases, bone can be regenerated by grafting fresh autogenous bone into the defect. Subsequently, we focused on the dentin of third molars, which are usually discarded after extraction, or teeth removed faor orthodontic therapy. As in bone, type I collagen is the main component of the organic matrix in dentin. Also, it has been proven that the organic matrix of dentin contains osteoinductive bone morphogenetic protein (BMP). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…The particle size of the hTDM reached in the current study was ranged between 350 and 500 μm to accommodate the defect size in consistent with clinical recommendations of using larger dentin particles for regenerative procedures [40]. This comes in agreement with Koga et al [39] and Togari et al [41] who demonstrated that the larger the particle size of TDM, the more prominent the bone regeneration as smaller particles implanted in bone defects had more resorbability, and they may have been resorbed in vivo before the initiation of new bone formation. In contrast, Chen et al [12] used hTDM as a paste for pulp capping with smaller particle size < 76 μm also showed that TDM paste could achieve the reparative procedure of dental pulp.…”
Section: Discussionsupporting
confidence: 91%
“…The particle size of the hTDM reached in the current study was ranged between 350 and 500 μm to accommodate the defect size in consistent with clinical recommendations of using larger dentin particles for regenerative procedures [40]. This comes in agreement with Koga et al [39] and Togari et al [41] who demonstrated that the larger the particle size of TDM, the more prominent the bone regeneration as smaller particles implanted in bone defects had more resorbability, and they may have been resorbed in vivo before the initiation of new bone formation. In contrast, Chen et al [12] used hTDM as a paste for pulp capping with smaller particle size < 76 μm also showed that TDM paste could achieve the reparative procedure of dental pulp.…”
Section: Discussionsupporting
confidence: 91%
“…Besides DDM particles, DDM blocks were also investigated [14,18,23,41,46]. In one study, DDM blocks with macropores were implanted into critical-sized iliac defects and new bone formation around the DDM had good union with the native bone [41].…”
Section: Ddm Preparationmentioning
confidence: 99%
“…Extensive studies have been conducted on DDM with its osteoinductivity and osteoconductivity in vitro and in vivo [17,18,[48][49][50][51]. In animal studies, DDM enhanced the bone healing process of tooth sockets, and promoted new bone formation in rat calvaria defects, rabbit parietal defects, minipig crania defects, sheep iliac defects, and porcine sinus [17,18,41,[47][48][49]52]. Besides bone, DDM was employed in osteochondral regeneration [20].…”
Section: Application Of Ddm In Bone Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…DDM and DBM are mainly type I collagen (95%); the remaining is made up of NCPs, including a small amount of growth factors. Briefly, DDM and DBM are acid-insoluble collagen-binding bone morphogenetic proteins (BMPs) [28][29][30] and fibroblast growth factors (FGFs) [31][32][33][34] (Figure 2).…”
Section: Characteristics Of Dentin and Bonementioning
confidence: 99%